2022
DOI: 10.1128/spectrum.02775-21
|View full text |Cite
|
Sign up to set email alerts
|

Transient Presence of Live Leptospira interrogans in Murine Testes

Abstract: Analysis of venereal transmission of Leptospira is important to determine if direct animal to animal transmission occurs, which could impact measures to prevent and treat leptospirosis. The goal of this study was to determine if live Leptospira colonize mouse testes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…An intriguing study in mice infected with Leptospira demonstrated that live culturable Leptospira may be present in the testes during the acute phase (not at 15 days post-infection). This finding raises the possibility of mammal-to-mammal venereal transmission [15]. The mechanisms of Leptospira pathogenesis are still elusive.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An intriguing study in mice infected with Leptospira demonstrated that live culturable Leptospira may be present in the testes during the acute phase (not at 15 days post-infection). This finding raises the possibility of mammal-to-mammal venereal transmission [15]. The mechanisms of Leptospira pathogenesis are still elusive.…”
Section: Discussionmentioning
confidence: 97%
“…Aseptic meningitis may present with a range of symptoms, from none to disorientation or obtundation. The incidence of aseptic meningitis can affect up to 80% of patients [15]. Renal symptoms, such as hematuria, pyuria, azotemia, and acute renal failure, may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Patoc (Supplementary Figure 1). Importantly, transient presence of Leptospira in low quantities has been shown previously in testes following infection before ultimate colonization of the kidney (Shetty et al, 2022). Therefore, the number of organisms is likely not biologically important due to the low overall burden in the heart.…”
Section: Intravenous Inoculation Leads To Reproducible Bacterial Burd...mentioning
confidence: 89%
“…Mouse strains exhibit differential susceptibility to infection by Leptospira . C3H/HeJ mice, a strain known to be susceptible to Leptospira , were selected for use in our short-term model of infection ( Poltorak et al., 1998 ; Nally et al., 2005 ; da Silva et al., 2012 ; Richer et al., 2015 ; Shetty et al., 2021 ; Shetty et al., 2022 ). It has long been known that TLR4 is important in controlling leptospirosis, as mice lacking TLR4 are susceptible to acute disease ( Pereira et al., 1998 ; Viriyakosol et al., 2006 ; Nair et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, this evidence was compiled, and the "Bovine Genital Leptospirosis" (BGL) syndrome was suggested as a disease dissociated from renal infection, rather than a secondary infection [13]. After that, the study of genital infection (even in other animal species) was performed by ours and other groups to confirm its agents, understand pathogenesis, and improve diagnosis methods and control protocols [33][34][35][36].…”
Section: Pathogenesis Of Leptospiral Infection In Bovinementioning
confidence: 99%